2015
DOI: 10.1007/s00198-015-3442-1
|View full text |Cite
|
Sign up to set email alerts
|

Are bone turnover markers associated with volumetric bone density, size, and strength in older men and women? The AGES–Reykjavik study

Abstract: Purpose The aim of this study was to examine the relationship between levels of bone turnover markers (BTM; osteocalcin (OC), C-terminal cross-linking telopeptide of type I collagen (CTX), and procollagen type 1 N propeptide (P1NP)) and quantitative computed tomography (QCT)-derived bone density, geometry and strength indices in the lumbar spine and femoral neck (FN). Methods A total of 1,745 older individuals (773 men and 972 women, aged 66-92 years) from the AGES-Reykjavik cohort were studied. QCT was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…From a clinical point of view, the dual source of BTM weaken the appropriate interpretation of their levels to identify patients with higher risk of fracture, as they reflect simultaneously bone fragility due to accelerated bone loss and a possible increase in bone strength because the resistance of the bone to bending or torsional forces is related exponentially to its diameter. Additional studies are needed to clarify the relationship of biological markers of bone metabolism and periosteal apposition, since our results demonstrated weak associations with increased CSA at different locations compared to our previous cross-sectional report [17]. At present periosteal bone biology is insufficiently understood, and should be the focus of research to assist the development of prevention and treatment options (including mechanical loading and osteoporosis drugs) of bone fragility.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…From a clinical point of view, the dual source of BTM weaken the appropriate interpretation of their levels to identify patients with higher risk of fracture, as they reflect simultaneously bone fragility due to accelerated bone loss and a possible increase in bone strength because the resistance of the bone to bending or torsional forces is related exponentially to its diameter. Additional studies are needed to clarify the relationship of biological markers of bone metabolism and periosteal apposition, since our results demonstrated weak associations with increased CSA at different locations compared to our previous cross-sectional report [17]. At present periosteal bone biology is insufficiently understood, and should be the focus of research to assist the development of prevention and treatment options (including mechanical loading and osteoporosis drugs) of bone fragility.…”
Section: Discussionmentioning
confidence: 59%
“…In two previous studies baseline bone formation and resorption markers were not significantly associated with cross-sectional data of bone size [29] or with the periosteal expansion rate at any skeletal site [9]. Previous cross-sectional studies in our laboratory and others have reported a positive association between BTM and proximal femur size [17,12]. …”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We adjusted our analyses for previously described variables (Marques et al 2016) that are potentially confounding or are known to be associated with muscle and bone quality or sleep duration. These included age, body mass index (BMI), smoking and physical activity status, self-reported mobility disability status, use of medications known to affect bone density, and total 25-hydroxyvitamin D (25OHD).…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] Bone mineral density (BMD), in turn, reflects the integrity of the bone tissue, being an indication of the structural remodeling capacity and, therefore, an index of the risk of propensity to the pathologies and lesions associated with the tissue. 1,4 At present, the loss of bone tissue integrity by the reduction of the mineral mass does not has been associated only with the aging process or hormonal disorders, but also with the reduction of fat mass (FM) and lean mass (LM), due to dietary interventions for body weight loss and sedentary lifestyle, respectively. 1,5,6 In general terms, resistance or resistive types of physical exercise tends to induce BMD changes due to mechanical stress on the bones, evidencing the exercise potential in the maintenance of BMC/BMD with aging.…”
Section: Introductionmentioning
confidence: 99%